Between Hot Rocks and Dry Places: The Status of the Dixie Valley Toad - Forrest, Matthew J.; Stiller, Josefin; King, Tim L.; Rouse, Greg W. (Western North American naturalist, 2017)
In Dixie Valley, Nevada, an isolated population of toads has been the subject of proactive conservation measures by the Nevada Department of Wildlife and the U.S. Fish and Wildlife Service since 2008 due to concerns about potential habitat degradation resulting from exploitation of nearby geothermal energy resources. These toads appear to belong within the Anaxyrus boreas species group but are commonly referred to as Dixie Valley toads (DVTs). The DVT is currently confined to an extremely narrow habitat range (370 ha) that is geographically isolated from any other A. boreas population. In this study, genetic variations in mitochondrial genes and 11 microsatellite loci were used to assess the affinities of DVTs in relation to members of the A. boreas species group. We compared results from DVTs with previously published data spanning much of the range of A. boreas in the United States and new data from a nearby toad population within Dixie Valley. Data from both mitochondrial DNA and microsatellites placed DVTs inside the A. boreas species group. In particular, DVTs fell into a cluster of A. boreas from Washington and California, along with other species from the A. boreas species group, namely A. nelsoni, A. canorus, and A. exsul. Genetic differentiation of DVTs was lowest between A. boreas populations in Washington and California. However, allele frequencies were significantly different between DVTs and all other populations, including a nearby locality within Dixie Valley. This genetic differentiation, along with the DVT's geographical isolation and restricted habitat, warrants recognition of the DVT as a distinct management unit.